2018
DOI: 10.3390/v10070375
|View full text |Cite
|
Sign up to set email alerts
|

Novel T7 Phage Display Library Detects Classifiers for Active Mycobacterium Tuberculosis Infection

Abstract: Tuberculosis (TB) is caused by Mycobacterium tuberculosis (MTB) and transmitted through inhalation of aerosolized droplets. Eighty-five percent of new TB cases occur in resource-limited countries in Asia and Africa and fewer than 40% of TB cases are diagnosed due to the lack of accurate and easy-to-use diagnostic assays. Currently, diagnosis relies on the demonstration of the bacterium in clinical specimens by serial sputum smear microscopy and culture. These methods lack sensitivity, are time consuming, expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The specific M. tuberculosis antigens screened from T7 phage displayed cDNA library may aid to develop a TB vaccine which could generate specific humoral response against M. tuberculosis (Talwar et al 2016). Talwar H et al developed a T7 phage cDNA library and constructed a microarray platform using sarcoidosis tissue to develop TB therapeutic or prophylactic (Talwar et al 2018). This was different from our study that the potential diagnostic antigen was screened from T7 phage displayed genomic DNA Library of M. tuberculosis.…”
Section: Discussionmentioning
confidence: 76%
“…The specific M. tuberculosis antigens screened from T7 phage displayed cDNA library may aid to develop a TB vaccine which could generate specific humoral response against M. tuberculosis (Talwar et al 2016). Talwar H et al developed a T7 phage cDNA library and constructed a microarray platform using sarcoidosis tissue to develop TB therapeutic or prophylactic (Talwar et al 2018). This was different from our study that the potential diagnostic antigen was screened from T7 phage displayed genomic DNA Library of M. tuberculosis.…”
Section: Discussionmentioning
confidence: 76%
“…Talwar et al identified 10 highly significant Mycobacterium tuberculosis (TB) clones of smear-positive pulmonary tuberculosis patients by using the T7 phage-display technique. This can be used as an immunogenic antigen of therapeutic or prophylactic vaccines and as a target for tuberculosis treatment [25].…”
Section: Discussionmentioning
confidence: 99%
“…With detection sensitivity of 0.999 and specificity of 0.959 [23] Mycobacterium tuberculosis infection With detection sensitivity of 1 and specificity of 1 [24] Foot-and-mouthdisease Identifying functional epitope VP1159-170 [25] Alzheimer'sdisease (AD) Identifying a panel of AD autoantibodies [26] Autoimmuneretinopathy By immunoprecipitation sequencing (PhIP-Seq) [27] Lung tumor Constructing lung tumor protein chip based on T7 phages [28] Melanoma By T7 phage display antigen microarrays [29] Detection of E. coli In water Detection of less than 10 CFU mL −1 E. coli in 3 h [30] In drinking water Detection of 1 × 10 4 CFU mL −1 within 2.5 h [31] In beverages Detecting alkaline phosphatase [32] In food and water Detecting alkaline phosphatase maltose-binding protein [33] In food matrices Detecting the overexpressed enzymes [34] E. coli Detecting the overexpressed luciferase [35] E. coli For phages and for antibiotic resistance testing [36] Detection of pathogens Viable bacterial pathogens By T7 phages carried tobacco etch virus (TEV) protease [37] Table 2. Review of targeted therapy based on T7 phage.…”
Section: Serological Biomarkers Cystic Fibrosismentioning
confidence: 99%
“…[118,119] By introducing the T7 phage display system into the detection of serological biomarkers, this new type of diagnostics can be more accurate, convenient, and efficient. [23][24][25][26][27][28][29][30][31][32][33] For example, Talwar et al isolated mRNA from leukocytes and bronchoalveolar lavage (BAL) cells of patients with nodule disease, and then extracted cDNA library of T7 phages. [23] They constructed a microarray platform, and screened serum from lung cancer patients, cystic fibrosis subjects, and healthy controls.…”
Section: Detection Of Serological Biomarkersmentioning
confidence: 99%